Leveraging climate information services to drive climate-smart agriculture and resilience across Southern Africa - Kabuya, Dorcas; Magagula, Futhi; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Centre for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA), in collaboration with the International Livestock Research Institute (ILRI), convened a regional policy dialogue session on “Leveraging Climate Information Services (CIS) to Drive Climate-Smart Agriculture (CSA) in the SADC Region” during the 2025 FANRPAN Policy Dialogue themed “Aligning Regional Policies and Investments for Accelerated Agri-food Systems Transformation in Africa.” The session brought together experts, policymakers, and practitioners to examine how CIS can enhance agricultural resilience, productivity, and adaptation in the face of increasing climate variability across Southern Africa. Opening remarks emphasized the importance of timely and reliable climate data as a foundation for sustainable agricultural decision-making. The keynote address highlighted the vulnerability of rain-fed agriculture in Southern Africa and demonstrated how CIS applications in Malawi, Zambia, and Zimbabwe have boosted productivity, reduced losses, and strengthened resilience. Discussions underscored the need for localized, user-oriented CIS, improved data infrastructure, and integration of CIS into national and regional agricultural policies. A panel discussion featuring experts explored the role of policy alignment, regional frameworks, and financing innovations in scaling CIS. Participants identified public–private partnerships, cross-border data harmonization, and targeted investments as key enablers for wider adoption of climate-smart practices. The audience contributed practical insights on sustainability, data integrity, farmer participation, and the inclusion of indigenous knowledge systems. The session concluded with a strong call to action for regional cooperation and policy coherence to scale up CIS as a strategic investment in agri-food system resilience. Key recommendations included establishing a cross-border CIS platform, integrating CIS within national adaptation plans, mobilizing climate finance, strengthening public–private partnerships, and documenting successful CSA practices for replication. Overall, the dialogue reaffirmed that effective climate information systems are vital to transforming agriculture in the SADC region, ensuring food security, and safeguarding livelihoods under changing climatic conditions.